ANALISIS KIMIA 9 JENIS KAYU INDONESIA - Gustan Pari; Hartoyo Hartoyo (Pusat Penelitian dan Pengembangan Hasil Hutan, 1990)
This paper deals with a chemical analyses of nine species of wood obtained from industrial plantation forest. The analyses comprised of the determination of holocellulose, cellulose, lignin, pentosan, moisture content, ash content, silica content and the solubility in cold water, hot water, one percent of sodium hydroxide and ethanol benzene (1:2) extractives.The result shows that holocellulose content ranges from 57,80 - 66,34 percent, cellulose content from 42,23 - 54,91 percent, lignin from 23,75 - 32,42 percent, pentosan from 10,10 -19,23 percent, moisture content from 10,19 - 26,37 percent, ash content from 0,25 - 3,08 percent, silica content from 0,07 - 2,47 percent, solubility in cold water ranges from 0,11 - 7,20 percent, solubility in hot water from 2,62 - 9,25 percent, solubility in 1% NaOH from 10,72-19,65 percent and ethanol benzene ranges from 2,09 - 6,13 percent.